2019
DOI: 10.1371/journal.pone.0202457
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress modifies the lactational performances and the urinary metabolomic profile related to gastrointestinal microbiota of dairy goats

Abstract: The aim of the study is to identify the candidate biomarkers of heat stress (HS) in the urine of lactating dairy goats through the application of proton Nuclear Magnetic Resonance (1H NMR)-based metabolomic analysis. Dairy does (n = 16) in mid-lactation were submitted to thermal neutral (TN; indoors; 15 to 20°C; 40 to 45% humidity) or HS (climatic chamber; 37°C day, 30°C night; 40% humidity) conditions according to a crossover design (2 periods of 21 days). Thermophysiological traits and lactational performanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…To the best of our knowledge, the effects of HS on microbial composition in broilers, laying hens, ducks, dairy goats and cows have been reported successively in recent two years [1923]. However, there is still unknown about the impact of HS on the pregnant sows’ microbial composition and its metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the effects of HS on microbial composition in broilers, laying hens, ducks, dairy goats and cows have been reported successively in recent two years [1923]. However, there is still unknown about the impact of HS on the pregnant sows’ microbial composition and its metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the effects of HS on microbial composition in broilers, laying hens, ducks, dairy goats and cows have been successively studied [1923]. However, few studies have been reported on the effects of HS on the gut microbial ecosystem of pigs, particularly in the pregnant sow.…”
Section: Introductionmentioning
confidence: 99%
“…However, glucose availability has been thought to limit milk yield during HS [ 3 ]. This is because heat-stressed animals suffer some degree of inflammation as they have a compromised intestinal barrier function [ 3 , 9 ], which results in intestinal-derived toxins infiltration that induces immune response. Consequently, glucose availability is significantly important because the activation of the immune system consumes large amounts of glucose [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study performed by Contreras-Jodar et al [ 57 ] demonstrated a significant influence of heat stress on microbiological homeostasis of the digestive system as well as milk yield and composition in goats; there were some changes in the thermo – physiological and milking characteristics of goats. An increase in the excretion of toxic compounds by digestive microorganisms and a decrease in the bioavailability of aromatic amino acids was observed.…”
Section: Impact Of Selected Stress Factors On Composition Of the Micrmentioning
confidence: 99%